Write an expression to describe the sequence below. Use n to represent the position of a term in the sequence, where n = 1 for the first term.

–7, –6, –5, –4, ...

an =

1 answer

The given sequence is as follows: -7, -6, -5, -4, ...

To find a formula for the n-th term of the sequence, observe that each term increases by 1.

The first term corresponds to n=1:

  • a1=7

The second term corresponds to n=2:

  • a2=6

The third term corresponds to n=3:

  • a3=5

The fourth term corresponds to n=4:

  • a4=4

We can see that the formula for the n-th term can be represented as:

an=7+(n1)

This simplifies to:

an=7+n1=n8

Thus, the expression for the n-th term of the sequence is:

an=n8